The Impact of Religiosity on the Malaysian Muslim Community’s Attitude Towards the Practice of Cupping - Hamza Abed Alkarim Hammad; Irwan Mohd Subri; Hasanah Abd Khafidz (Institut Agama Islam Negeri Batusangkar, 2023)
This study identifies the Muslim Malaysian community’s attitudes towards cupping therapy in contrast with some variables such as: Gender, Age, Residence, Marital status, and Academic achievement. To achieve this goal, the researcher made a questionnaire consisting of 20 paragraphs, and it was distributed electronically randomly, during the period ranging from 10-8-2021 to 9-2- 2022, and the number of respondents to this questionnaire was 420 individuals. The results of the study showed a positive trend towards cupping in the Malaysian society, also, showed there are statistically significant differences in the attitudes of the Malaysian society towards cupping due to a variable Gender and Age, there are not statistically significant differences in the attitudes of the Malaysian society towards cupping due to a variable Marital Status, Higher Education, State of Residence and Living Area. The inclination of the Malaysian Muslim community towards cupping therapy (Hijama) confirms the desire of Muslims to emulate the Prophet (Peace be Upon Him) in this practice. As such, this study does not seek to explain the importance of Hijama, but it came to confirm that Muslim communities are interested in following the Prophetic Sunnah, so it is a practical study of Sharia, concerned with practical application for this type of therapy. Moreover, the study is based on the purposes (Maqasid) of Sharia, as the results of the study showed that cupping therapy has practical benefits in the health of the body, and the protection of the body and soul are derived from the Maqasid Sharia.